The Effect of Differentiated Learning And Ice Breaking on The Outcomes Of Science Learning of Grade Iv Elementary School Students in Tomohon Selatan District - Wilar, Feibe Imelda; Rorimpandey, Widdy HF; Pangkey, Richard DH (Abdurrauf Science and Society, 2025)
This study aims to describe the effect of differentiated learning and breaking on the learning outcomes of science and natural sciences in grade IV elementary school students in South Tomohon District. The background of this study is based on the fact that students have diverse learning characteristics, while the learning approaches used in class still tend to be uniform. On the other hand, science and natural sciences learning requires active involvement and psychological readiness of students, which are often not optimally developed. This study uses a quantitative method with a quasi-experimental design in the form of a pretest-posttest control group design. The subjects of the study were grade IV elementary school students who were selected purposively. The instruments used were learning outcome tests referring to indicators of science learning achievement and observation sheets for learning implementation. The results of the data analysis showed that there was a significant difference in the results of learning science between students who participated in differentiated learning accompanied by ice breaking and students who participated in conventional learning. The application of differentiated learning helps students learn according to their needs and learning styles, while ice breaking has been proven to improve the pleasant classroom atmosphere and students' mental readiness to learn. These two strategies synergistically provide a positive contribution to improving student learning outcomes. Thus, it can be concluded that the implementation of differentiated learning combined with ice breaking has a significant effect on the learning outcomes of elementary school students. This finding recommends that teachers adopt a learning approach that is responsive to the individual needs of students and pays attention to psychological aspects in the learning process.